Selected Water Quality Parameters, Its Relation With Zooplankton Community And Fatty Acid Content At Jelutong, Pulau Jerejak And Kuala Juru - Kassim, Nur'Ain (2014)
This study was carried out to determine the water quality characteristics of coastal waters around Penang island, and its relation with zooplankton community and fatty acid content. Three sampling stations were selected, namely Kuala Juru (Juru Station), Jelutong (Jelutong Station) and Pulau Jerejak (Jerejak Station). Water and zooplankton samples were collected on five sampling occasions from July 2009 until April 20 II. Physico-chemical parameters measured in this study were temperature, salinity, pH, dissolved oxygen (DO), biochemical oxygen demand (BOD), chlorophyll-a, ammoniacal-nitrogen and nitrite-nitrogen. Zooplankton samples were collected by horizontal towing with plankton net (WP-2). A total of 8 phyla and 37 zooplankton genera were recorded at those three sampling locations. Phylum Arthropoda dominated the whole locations with 78.80% of relative abundance, where Copepoda was the most abundant. Other phyla which were Chordata (9.10%), Cyliophora (6.12%), Actinopoda (2.08%), Rotifera (2.57%), Annelida (0.63%), Cnidaria (0.51 %), and Chaetognatha (0.19%) were accounted in small abundance. Juru Station, which is highly impacted by human activities, had the highest relative abundance and Jerejak Station (control station and considered to have low impact by anthropogenic activities) had the lowest relative abundance. Zooplankton diversity was quite low at all stations, might be due to large abundance of dominant taxa. The dominant fatty acid methyl esters (FAMEs) detected on XIII plankton consisted of SAFA (CI6:0, C14:0 and CI8:0), MUFA (CI6:0, C14:0 and C 18:0), PUFA (C 18:2n6c and C20:3n6) and HUFA (C22:6n3 or DHA).